STUDENTS’ MOTIVATIONS TOWARD CHOOSING ENGLISH EDUCATION - Choiril Anwar; Kurniawan Yudhi Nugroho (University of Kuningan, 2018)
Motivation, almost at all aspects, gives a big impact for senior high school students to choose a major or study program at a university. The motivation itself can be both intrinsic and extrinsic. This study aims to investigate the motivation of students to choose English Education department at university. The subjects and sample of this research were 37 students of batch of 2015 and 2016 majoring in English Education of Sultan Agung Islamic University (UNISSULA) Semarang, Indonesia. This is descriptive quantitative research. Observations and questionnaires were used to collect the data needed. The data was then analyzed by using descriptive statistical analysis. As results, it was eventually found that 81.1% of the students of English Education have strong intrinsic motivation which leads them to choose English Education as their major. This selection was due to students’ curiosity and passion to increase their potential and skills in English.Keywords: English education, students’ motivation, university